Influence of soil mechanical and hydraulic parameters on the definition of rainfall intensity and duration thresholds based on Transient rainfall infiltration and grid-based regional slope-stability model (TRIGRS) - Zhang, Sen; Jiang, Qigang; Xu, Xitong; Tao, Guofang; Zhang, Zhenchao; Gao, Xin; He, Chunlong (Frontiers in Earth Science, 2022)
As the supplement to empirical-statistical methods, physically based methods can be employed to define rainfall thresholds for triggering landslides in areas lacking records of landslides. Transient Rainfall Infiltration and Grid-Based Regional Slope-Stability model (TRIGRS), as a physically based model, has been applied to define rainfall thresholds at the basin, slope unit, and grid cell scales. However, as far as we know to date, the influence of soil mechanical and hydraulic parameters on defining rainfall thresholds at various scales has not been comprehensively evaluated. In this study, TRIGRS was used to define rainfall intensity(I) and duration(D) thresholds at various scales for Buzhe village, Pu’an county, Guizhou province, China under the conditions of different soil physical parameters. The results show that the number of rainfall thresholds decreased with cohesion (c) and internal friction angle (φ) and increased with soil unit weight (γ_s), excluding the basin scale. Threshold position varied positively with c and φ and negatively with γ_s. Soil mechanical parameters have a greater influence on the definition of rainfall thresholds based on TRIGRS than hydraulic parameters.